The ribosomal protein genes and Minute loci of Drosophila melanogaster. - Marygold, S.J.; Roote, J.; Reuter, G.; Lambertsson, A.; Ashburner, M.; Millburn, G.H.; Harrison, P.M.; Yu, Z.; Kenmochi, N.; Kaufman, T.C.; Leevers, S.J.; Cook, K.R. (Genome Biology, 2007)
Mutations in genes encoding ribosomal proteins (RPs) have been shown to cause an array of cellular and developmental defects in a variety of organisms. In Drosophila melanogaster, disruption of RP genes can result in the 'Minute' syndrome of dominant, haploinsufficient phenotypes, which include prolonged development, short and thin bristles, and poor fertility and viability. While more than 50 Minute loci have been defined genetically, only 15 have so far been characterized molecularly and shown to correspond to RP genes.We combined bioinformatic and genetic approaches to conduct a systematic analysis of the relationship between RP genes and Minute loci. First, we identified 88 genes encoding 79 different cytoplasmic RPs (CRPs) and 75 genes encoding distinct mitochondrial RPs (MRPs). Interestingly, nine CRP genes are present as duplicates and, while all appear to be functional, one member of each gene pair has relatively limited expression. Next, we defined 65 discrete Minute loci by genetic criteria. Of these, 64 correspond to, or very likely correspond to, CRP genes; the single non-CRP-encoding Minute gene encodes a translation initiation factor subunit. Significantly, MRP genes and more than 20 CRP genes do not correspond to Minute loci.This work answers a longstanding question about the molecular nature of Minute loci and suggests that Minute phenotypes arise from suboptimal protein synthesis resulting from reduced levels of cytoribosomes. Furthermore, by identifying the majority of haplolethal and haplosterile loci at the molecular level, our data will directly benefit efforts to attain complete deletion coverage of the D. melanogaster genome.